Corrigendum: Natural killer cells from patients with recombinase-activating gene and non-homologous end joining gene defects comprise a higher frequency of CD56bright NKG2A+++ cells, and yet display increased degranulation and higher perforin content [Front Immunol, 8, (2017), (798)] doi: 10.3389/fimmu.2017.00798 - Dobbs, K (2020)
10.3389/fimmu.2017.01244